Offshoring, Inward Investment and Export Performance in Ireland - BARRY, FRANK; BERGIN, ADELE (ESRI, 2012)
Ireland is one of the most FDI-intensive economies in the OECD and is a significant export platform for both manufacturing and internationally traded services. This chapter provides case studies of three of the most important FDI-intensive manufacturing sectors ? ICT, pharmaceuticals and medical devices ? and two of the substantially foreign-owned internationally traded services segments ? software & IT and international financial services. It also updates earlier analyses of how Ireland's inward FDI sectors have fared over the course of the global financial crisis.
PUBLISHED
Keywords: Offshoring; Investment; Export Performance